The emerging role of cellular senescence in amyotrophic lateral sclerosis - Tan, Xingli; Gao, Naiyong (Frontiers in Neuroscience, 2025)
Cellular senescence is a state of permanent cell cycle arrest and is considered a key contributor to aging and age-related diseases, including amyotrophic lateral sclerosis (ALS). The physiological processes of aging lead to a variety of molecular and cellular phenotypes, and evidence of overlap between ALS and aging-related biomarkers suggests that cell type-specific senescence may be a critical factor in ALS. Senescent microglial cells, astrocytes, and neurons have been detected in ALS patients and animal models. However, while accumulating evidence suggests a potential link between cellular senescence and ALS, this connection remains not yet conclusively established. Importantly, how senescent cells may contribute to the neuropathophysiology of ALS remains largely unknown. Additionally, the growing popularity of anti-aging therapies has highlighted the potential of senescent cell clearance as a promising strategy for treating age-related diseases, including ALS. This review provides an overview of cellular senescence, discusses recent advances in understanding how senescence in different cell types influences ALS pathogenesis, and explores the potential role of anti-senescence therapies in ALS treatment.